The new consumers : the influence of affluence on the environment - Myers, Norman. (Island Press, 2004)
"The environmental analyst Norman Myers and his coauthor Jennifer Kent here concentrate not on nations like the United States but on the stunning increase in what they term "new consumers" - people in developing and transition nations who have achieved sufficient affluence to enjoy middle class lifestyles, including buying cars, eating meat regularly, and using a host of household electrical appliances. Even in the midst of great inequity, these New Consumers have already gained purchasing power equal to that of the United States, and the cumulative impact on the environment is enormous." "Myers and Kent have distilled the results of their remarkable research to reveal the patterns of increasing consumption in twenty developing and transition nations, with particular attention to China and India, whose surging economies and large populations account for much of the recent exceptional growth in humanity's ecological footprint. New Consumers generally have been following a path established in long-developed nations of needlessly overusing limited natural resources. As the authors document, this course is clearly unsustainable on a world scale. When India's economy doubled, its air pollution rose eightfold. Were each person in China to consume as much grain-fed beef as today's average American, it would require more grain than the entire U.S. harvest." "If the developed nations have set a dangerous precedent by overconsuming, innovative policies offer some reason for hope. China, for example, has now written sustainable consumption into law and begun promoting it through economic incentives and education programs. Drawing on such examples, Myers and Kent outline an alternative path. Through a combination of lifestyle changes, policy reforms, and technological innovation around the globe, a decent and enduring standard of living could be available to everyone."--BOOK JACKET.